Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1111/and.12502
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of sperm antigens using serum samples from individuals with and without antisperm antibodies

Abstract: The aim of the study was to identify human sperm antigens reacting with polyclonal antisperm antibodies. Protein sperm extracts were subjected to electrofocusing, and next immune reactions (immunoblotting) were carried out with positive for antisperm antibodies and control (not containing antisperm antibodies) serum samples. Proteomic analysis of human sperm proteins resulted in identification of 80 sperm antigens that could be divided into three groups: antigens specific for patients with antisperm antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Three of these proteins (ACR, GAPDHS, and ODF1) are strictly present on spermatozoa, making them good sperm-cell-specific antigens. Among the sperm antigens identified, several are known to be involved in key steps of the fertilization process, such as HSPA1L [ 61 ], CCT3 [ 62 ], ZPBP and ZPBP2 [ 63 ], and HSPD1 [ 64 , 65 ]. Others, such as AKAP3 and ROPN1, are associated with the acrosomal reaction process [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three of these proteins (ACR, GAPDHS, and ODF1) are strictly present on spermatozoa, making them good sperm-cell-specific antigens. Among the sperm antigens identified, several are known to be involved in key steps of the fertilization process, such as HSPA1L [ 61 ], CCT3 [ 62 ], ZPBP and ZPBP2 [ 63 ], and HSPD1 [ 64 , 65 ]. Others, such as AKAP3 and ROPN1, are associated with the acrosomal reaction process [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, PGK2 and ACRBP were found to react to seminal plasma of immunoinfertile men and sera of vasectomized patients respectively. The other research also indicated that ENO1 reacted to both antisperm antibody-positive and -negative sera, whereas ACRBP did only to the positive serum, but not to the negative [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sera containing ASAs have been utilized to identify the relevant antibody‐mediated infertility immune dominant antigens (Shetty et al, ). These included HSP70, tubulin α 1a, class 4b β‐tubulin, ATP synthase subunit β, carbonic anhydrase 2, α‐enolase, and lactate dehydrogenase (LDHC) (Nowicka‐Bauer et al, ). Western blot analysis has been used to quantify these antigens and to identify protein–protein interactions (Auer, Senechal, Desvaux, Albert, & De Almeida, ).…”
Section: Diagnostic Methods To Identify Immune Regulatory Moleculesmentioning
confidence: 99%
“…These include T‐complex protein 1 subunit θ, arylsulfatase A, and arrestin domain‐containing protein‐5. Since these proteins are involved in spermatozoon–oocyte interaction (Nowicka‐Bauer, Kamieniczna, Cibulka, Ulcova‐Gallova, & Kurpisz, ), presence of ASAs against these proteins may result in failure of sperm‐zona binding and infertility.…”
Section: Testicular Immune Mechanismmentioning
confidence: 99%